2020
DOI: 10.3390/jmse8110944
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Coastal and Submarine Groundwater Processes: Controls and Environmental Impact on the Thriassion Plain and Eleusis Gulf (Attica, Greece)

Abstract: This study focuses on the hydrogeological conditions in the coastal (Thriassion plain) and submarine (Eleusis Gulf) environment of West Attica, Greece. Up to now, the predominant aspect for the Thriassion plain groundwater—hosted within the Neogene-Quaternary sediments—was its direct hydraulic contact with the seawater. Due to that, the coastal plain groundwater is strongly believed to be of brackish quality irrespective of the local hydrodynamic conditions. Our major goal is to evaluate the actual mechanism c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…In the absence of human intervention, water quality changes are caused by natural processes such as bedrock evapotranspiration and wind-deposited dust [138]. Water's physical and chemical composition may vary due to natural processes including soil erosion and runoff, as well as hydrological variables that cause runoff and biological activities in aquatic environments [139][140][141][142]. The Indus River's natural environment may include both dissolved and undissolved elements as a result of natural processes [125], thus this information should be taken into consideration.…”
Section: Influence Of Natural and Anthropogenic Factors On Hydrogeologymentioning
confidence: 99%
“…In the absence of human intervention, water quality changes are caused by natural processes such as bedrock evapotranspiration and wind-deposited dust [138]. Water's physical and chemical composition may vary due to natural processes including soil erosion and runoff, as well as hydrological variables that cause runoff and biological activities in aquatic environments [139][140][141][142]. The Indus River's natural environment may include both dissolved and undissolved elements as a result of natural processes [125], thus this information should be taken into consideration.…”
Section: Influence Of Natural and Anthropogenic Factors On Hydrogeologymentioning
confidence: 99%
“…The latter is comprised of limestones, dolomitic limestones and dolomites. The Cretaceous and Triassic aquifers flow to the southwest and discharge partly through coastal springs near the city of Eleusis and the entire North-Western coastline of the Eleusis Gulf and partly into Neogene-Quaternary deposits [39,40]. From this field work, the seasonal water level fluctuations in the unconfined aquifer were measured 0.4-0.5 m and within the confined aquifers 1.2-1.5 m. A conceptual model of the deposits in Figure 3 illustrates the multi-level aquifer conditions within the Pleistocene strata, where lenticular intercalation consists of a water-yielding formation [31].…”
Section: Geology and Hydrogeological Characteristics Of The Study Areamentioning
confidence: 99%
“…In addition, some researchers point out that other factors relating to urban land can affect water quality, such as erosive rainfall events, heavy metals in surface sediments, natural biological filtration devices, and the landscape pattern of the surrounding zones in the urban area. These water quality studies have identified key variables that affect the physical, chemical, and biological processes of surface water bodies [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%